2008
DOI: 10.1111/j.1440-1746.2008.05346.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of gastric cancer detected by endoscopy as part of annual health checkup

Abstract: Background and Aim: Upper gastrointestinal endoscopy is generally accepted as the gold standard for the clinical evaluation of gastric cancer (GC). However, the efficacy of endoscopic screening for asymptomatic GC remains controversial. The present study is designed to clarify the efficacy of endoscopic screening for the detection of early GC by investigating the clinicopathological features. Methods: A total of 17 522 patients who had underwent endoscopic screening as a part of their annual health checkup at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 20 publications
2
30
0
Order By: Relevance
“…However, the rate of false-negative results associated with the detection of gastric cancer via endoscopy was higher than expected, and endoscopic diagnosis of EGC is difficult because often only subtle changes occur, which are not observed on endoscopic examination. Hosokawa et al [15] reported that the rate of false-negative results for the detection of EGC while using gastroscopy was 25.8 % at 3 years, and Aida et al [16] reported that endoscopic screening identified six of 26 gastric cancer (23.1 %) as missed lesion on previous endoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the rate of false-negative results associated with the detection of gastric cancer via endoscopy was higher than expected, and endoscopic diagnosis of EGC is difficult because often only subtle changes occur, which are not observed on endoscopic examination. Hosokawa et al [15] reported that the rate of false-negative results for the detection of EGC while using gastroscopy was 25.8 % at 3 years, and Aida et al [16] reported that endoscopic screening identified six of 26 gastric cancer (23.1 %) as missed lesion on previous endoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…1 Even now, however, some patients are detected with advanced-stage disease. During gastrectomy for advanced gastric cancers, it is important to diagnose surgical curability and to avoid excessive surgery, which is a risk factor for complications and has the potential to decrease survival.…”
mentioning
confidence: 98%
“…Such cancers are often missed by EGD; the reported miss rate for gastric cancers is approximately 20%. 4 Although image-enhanced endoscopic technologies such as narrow-band imaging (NBI) 5 and flexible spectral imaging color enhancement (FICE) 6 have been developed, they are not sufficient to improve the detection rate of gastric cancers.…”
Section: Introductionmentioning
confidence: 99%